Pengaruh Berakhirnya Wabah Covid-19 Terhadap Perekonomian UMKM di Kota Surakarta - Farah Dina Eka Putri; Sapta Mei Budiyanto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study aims to determine the effect of the end of the Covid-19 outbreak on the economy of MSMEs (Micro, Small and Medium Enterprises) in Surakarta City. This research method is a qualitative method with a descriptive approach. Data were collected through participatory observation, in-depth interviews and document studies. Informants in this study consisted of MSME (Micro, Small and Medium Enterprises) owners, MSME (Micro, Small and Medium Enterprises) workers and other MSME (Micro, Small and Medium Enterprises) actors. The results showed that the Covid-19 pandemic had a significant negative impact on the economy of MSMEs in Surakarta City. The solutions proposed to overcome this problem include social protection, tax reduction, and infrastructure development. This research is expected to provide important information for the government, entrepreneurs and workers of MSMEs (Micro, Small and Medium Enterprises) about the negative impact of the end of the Covid-19 outbreak on the economy of MSMEs (Micro, Small and Medium Enterprises) in Surakarta City, and assist the government in determining the right strategy to promote the economy of MSMEs (Micro, Small and Medium Enterprises) in the region.